Effects of Higher Education Reforms: Change Dynamics
VI, 312 p.
Keywords: Higher education is in transition. On the one hand, over the last decades it has become politically and economically more important and thus also an object of reforms. On the other hand, higher education has become less special and is no longer able to justify its unique governance arrangements. This volume presents a collection of contributions that go beyond reform agendas as such and focus on the effects of reforms at all relevant levels in higher education systems. It is organised in four themes – education, research, governance, and academic profession – with a variety of levels of analysis, theoretical perspectives, methodological approaches and geographical foci. The topics in focus include the possible impact of latest national and European initiatives, changes in the primary processes (education and research) on the levels of institutions, professions and for individuals as well as higher education dynamics in contexts often overlooked in the literature (e.g. Africa). The aim is to ‘take stock’ of the growing knowledge basis with respect to higher education with a special focus on the influence of reforms on the key aspects of higher education.